Gender dimensions in the coordinate system of public management and administration - Muratbaieva, Hulbarchyn; Nikolaiev, Vladyslav; Vasylieva, Oleksandra Illivna; Vasylieva, Nataliia Viktorivna; Moskalenko, Svitlana (Національна академія правових наук України. Національний юридичний університет імені Ярослава Мудрого, 2021)
Nowadays, constitutional reforms are continuing, which are aimed at the development of a democratic state governed by the rule of law and European integration. Equal rights and opportunities for both genders constitute one of the fundamental principles of democracy and respect for the individual. Gender equality permeates all the provisions of the Constitutions of Kyrgyzstan and Ukraine. In fact, the Fundamental Law determines the gender strategy for the state. The most important line of the women's movement in recent years has been lobbying for necessary changes in laws and draft laws related to gender issues. The study analyses some aspects of women's representation in the activities of government bodies in Ukraine and the Kyrgyz Republic. The study presents theoretical and practical opinions, expert assessments on the representation of women in a state governed by the rule of law. The problems of reforming the legislation and the foundations of public relations since the beginning of the 1990s and up to the present time are also addressed, leading to a rethinking of the essence of gender equality and contributing to the activation of the development of new approaches to legal regulation in the given subject area. During the analysis, it was noted that to perform international obligations to achieve gender equality in the countries under study, constitutional framework and guarantees of adherence to the principle of equality were developed, which is also constituted in the provisions of the Fundamental Law of the Kyrgyz Republic and the Constitution of Ukraine.

Сьогодні тривають конституційні реформи, спрямовані на розвиток демократичної держави, що керується верховенством права, та європейську інтеграцію. Рівні права та можливості для обох статей є одним з фундаментальних принципів демократії та поваги до особистості. Гендерна рівність пронизує всі положення Конституцій Киргизстану та України. Фактично, Основний Закон визначає гендерну стратегію для держави. Найважливішим напрямком жіночого руху останніх років стало лобіювання необхідних змін до законів та законопроектів, пов'язаних з гендерними питаннями. У дослідженні аналізуються деякі аспекти представництва жінок у діяльності органів влади в Україні та Киргизькій Республіці. У дослідженні представлені теоретичні та практичні думки, експертні оцінки щодо представництва жінок у правовій державі. Також розглядаються проблеми реформування законодавства та основ суспільних відносин з початку 1990-х років і до теперішнього часу, що призводить до переосмислення сутності гендерної рівності та сприяє активізації розробки нових підходів до правового регулювання у цій предметній галузі. Під час аналізу було зазначено, що для виконання міжнародних зобов'язань щодо досягнення гендерної рівності в досліджуваних країнах було розроблено конституційну базу та гарантії дотримання принципу рівності, що також закріплено в положеннях Основного Закону Киргизької Республіки та Конституції України.
Keywords: gender equality; electoral rights; balance; women's participation; human rights; гендерна рівність; виборчі права; баланс; участь жінок; права людини